A CEPHALOMETRIC INVESTIGATION OF THE EFFECTS OF THE ELASTIC BITE-BLOCK IN THE TREATMENT OF CLASS-II DIVISION-1 MALOCCLUSIONS - (:unkn) unknown (OXFORD UNIV PRESS UNITED KINGDOM, 1995)
The purpose of this study was to investigate cephalometrically, the effects of a functional appliance-headgear combination, the Elastic Bite-block (EBB). Of 50 Class II division 1 subjects who participated in this study, 30 made up the treatment group and 20 the control group. All of the selected cases exhibited mandibular retrognathism, facial growth pattern either along the Y-axis or in the horizontal direction, and were all at the peak of the prepubertal growth spurt. Whilst the EBB was applied to the treatment group for 1 year, no treatment was performed on the control group. Measurements made on the lateral cephalograms, obtained at the beginning and end of the study were statistically evaluated. The following changes took place as a result of EBB treatment: sagittal growth of the maxilla was inhibited, the upper molars were distalized and intruded, sagittal growth of the mandible was stimulated and the lower molars erupted in a mesio-occlusal direction. As a result of downward and backward rotation of the mandible, the vertical dimension showed incremental changes. The upper and the lower incisors were both uprighted and intruded, and overjet and overbite decreased.
Keywords: GROWTH